Comparison of the Verb Biti (to Be) in Slovenian and Russian Languages - Oman, Jera (Slovenski jezik / Slovene Linguistic Studies, 2024)
This article explores the verb biti in Slovenian and Russian languages from the perspective of their semantic and syntactic characteristics. In light of the connectedness of the two languages, it is reasonable to expect that the use of the verb biti in Slovenian and быть in Russian is similar. With regard to that, the study is focused on the search for similarities and differences resulting from different linguistic norms. The verb is multidimensional in both languages and as such, acts in three cardinal capacities; as a full verb, as a grammatical conjunction or as an element of a compound form. This multidimensionality advances its widespread use in Slovenian and Russian languages. The semantic account of the verbs biti and быт presented in this article is based on the example of translating certain constructions from Russian to Slovenian language and the syntactic and semantic intertwining of the verbs biti and imeti. The account also analyses the role of a conjunction as exercised by the verb biti, with particular attention dedicated to the issue of zero copula in Russian language.